2020
DOI: 10.1101/2020.02.19.20025296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Prediction of Disease Progression in 2019 Novel Coronavirus Pneumonia Patients Outside Wuhan with CT and Clinical Characteristics

Abstract: Conclusion: CT severity score was associated with inflammatory levels and higher NLR and CT severity score on admission were independent risk factors for short-term progression in patients with NCP outside Wuhan. Furthermore, early admission and surveillance by CT should be recommended to improve clinical outcomes.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 23 publications
4
46
0
1
Order By: Relevance
“…This indicates that the diversity of the initial lesions in severe patients was not solely due to GGO lesion caused by exudation, but also due to a large number of consolidations. This present study finding was consistent kjronline.org with that of a previous report, in which severe patients had a larger lung lesion involvement (i.e., total lesion CT score) than that in non-severe patients (25). The total lesion score on CT quantitatively represents the percentage of lung parenchyma, demonstrating evidence of abnormalities as a whole and assesses of the total extent of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that the diversity of the initial lesions in severe patients was not solely due to GGO lesion caused by exudation, but also due to a large number of consolidations. This present study finding was consistent kjronline.org with that of a previous report, in which severe patients had a larger lung lesion involvement (i.e., total lesion CT score) than that in non-severe patients (25). The total lesion score on CT quantitatively represents the percentage of lung parenchyma, demonstrating evidence of abnormalities as a whole and assesses of the total extent of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the present study also revealed significant positive correlations between CT quantitative parameters and neutrophil percentage, hs-CRP levels, and procalcitonin levels. These results were consistent with those of another report (25). Neutrophil percentage and C-reactive protein levels may be correlated to the cytokine storm induced by viral infection (6) and increased procalcitonin level may be due to secondary bacterial infection (27).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, only seven easy-access features were included in our nomogram, including older age, higher LDH and CRP, DBIL, RDW, BUN, and lower ALB. Age, NLR and LDH has been reported to be risk factors for severe patients with SARS-CoV-2 infection [3,[5][6][7]. NLR, a widely used marker for the assessment of system inflammation, was not identified by LASSO as an important feature instead of LDH and CRP, which are associated with the systemic inflammatory response [8].…”
Section: Discussionmentioning
confidence: 99%
“…30 studies were included in the qualitative synthesis and meta-analysis [ Figure 1]. [3,8,[17][18][19][20][21][22][23][24][25][26]9,[27][28][29][30][31][32][33][34][35][36][10][11][12][13][14][15][16] There were a total of 6452 patients from 30 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%